2006
DOI: 10.1021/la061772x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Crystallization at the Air−Water Interface:  An Unusual Feature of Gemini Surfactant with a Rigid Spacer

Abstract: An unusual feature which involves spontaneous crystallization at the air-water interface from aqueous solution was reported for a water-soluble gemini surfactant with xylyl spacer, (p-phenylenedimethylene) bis(dodecyldimethylammonium) dibromide. Polarizing microscope, in situ confocal microscopic Raman spectroscopy, and powder XRD were used to characterize the structure of the crystal and investigate the driving force for nucleation. It was inferred that, besides the surface enrichment of amphiphiles and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Recently, there have been a few reports concerning the crystallization of a single compound at the air/solution interface (Kadam et al, 2011;Zhou et al, 2006). Kadam et al (2011) found that paracetamol might form single crystals at the air/ liquid interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been a few reports concerning the crystallization of a single compound at the air/solution interface (Kadam et al, 2011;Zhou et al, 2006). Kadam et al (2011) found that paracetamol might form single crystals at the air/ liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…Kadam et al (2011) found that paracetamol might form single crystals at the air/ liquid interface. In our previous work, we discovered that p-xylylenebis(dodecyldimethylammonium bromide) (12-Ar) ISSN 1600-5767 # 2015 International Union of Crystallography with a rigid (xylylene) spacer could be used to fabricate an interfacial crystal with a small size (Zhou et al, 2006). Since a soluble surfactant can spontaneously form a Gibbs monolayer at the air/liquid interface, we were led to hypothesize that the Gibbs monolayer of soluble amphiphiles has an important effect on the interfacial crystallization as the Langmuir monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it suggests the importance of hydrogen bonds for the stability of the aggregations as well as their influence on the aggregation morphology. The existence of rigid segments refers to mesogenic groups endowed with sufficient anisotropy in both attractive and repulsive forces to contribute strongly to the liquid‐crystal phase formation ,. Upon the introduction of biphenyl groups, the Van Der Waals Interactions between the surfactant moleciles can be enhanced, subsequently resulting in stable self‐assembled aggregations.…”
Section: Resultsmentioning
confidence: 99%
“…1,7,[22][23][24][25][26][27][28] For instance, Zhang et al 29 once found self-organized domains in a ring pattern of a samarium complex bound by a β-diketone ligand TTA-Sm(TTA) 3 Phen (TTA denotes thenoyltrifluoroacetone; Phen denotes 1,10-phenanthroline). Stearic acid was mixed with the samarium complex, which formed highly ordered round domains.…”
Section: Resultsmentioning
confidence: 99%